PEREMPUAN DAN SAINS: SEKSISME DALAM PENDIDIKAN SAINS DI SEKOLAH ISLAM YOGYAKARTA - Sa'dan, Masthuriyah (UIN Raden Mas Said Surakarta, 2019)
This study aims to analyse sexism in science education at two Islamic schools in the specialised area of Yogyakarta, namely in MTs Assalafiyyah Mlangi Sleman and Ali Maksum Krapyak Bantul. This study uses an ethnographic approach with data collection techniques of observation, interviews, and surveys. The results showed that science was partial to boys due to gender giving birth to sexism in science education. Discrimination based on sex is not a good thing and is contrary to scientific ethics, namely science for all genders. However, the fact this sexism behaviour also spreads in all lines of people's lives. Without realising the difference in giving and treatment of girls and boys in science is considered as something healthy and so it is. So, to minimise such conditions, we need synergy between all elements of government, school principals, teachers, parents, and society, that girls have the right to master science and technology the same as boys.